Legality of Prenuptial Agreements: The Role of Notaries in Guaranteeing Legal Certainty - Erlangga Damarjati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Prenuptial agreements serve as essential legal instruments that define financial arrangements and property rights between spouses before marriage. However, their enforceability and legal certainty depend heavily on compliance with legal formalities, particularly the role of notaries in ensuring their validity. This research examines the legal framework governing prenuptial agreements and the crucial function of notaries in guaranteeing legal certainty. Through a normative-juridical approach, this study analyzes statutory regulations, case law, and legal doctrines to highlight the importance of notarization in preventing disputes and ensuring enforceability. The findings reveal that notarial authentication plays a fundamental role in verifying the legal capacity of parties, ensuring mutual consent, and fulfilling formal requirements mandated by law. Additionally, the study identifies common legal challenges, including improper drafting, non-compliance with formalities, and potential fraudulent practices, which may render agreements void or unenforceable. To enhance the legal certainty of prenuptial agreements, this research recommends strengthening notarial regulations, improving legal awareness among couples, and reinforcing judicial oversight. Ultimately, the study underscores the significance of notarial involvement as a preventive legal measure to uphold the integrity and enforceability of prenuptial agreements in marital and financial planning.